Enhanced mass transfer of pulsed vacuum pressure pickling and changes in quality of sour bamboo shoots - Dai, Jian-Wu; Zhang, Qing; Li, Ming; Li, Lian-Jie; Xu, Li-Jia; Liu, Yao-Wen; Yin, Peng-Fei; Liu, Shu-Xiang; Zhao, Yong-Peng; Gou, Kai-Yun; Li, Ying-Lu; Qin, Wen (Frontiers in Microbiology, 2022)
Sour bamboo shoot is a traditional Chinese fermented vegetable food. The traditional pickling method of sour bamboo shoots has the disadvantages of being time-consuming, inhomogeneous, and difficult to control. Pulsed vacuum pressure pickling (PVPP) technology uses pulsed vacuum pressure to enhance the pickling efficiency significantly. To demonstrate the effects of salt content and PVPP technical parameters on the fermentation of bamboo shoots, the sample salinity, pH value, color, crunchiness and chewiness, nitrite content, and lactic acid bacteria content during the pickling process were investigated. The salt content inside the bamboo shoots gradually increased to the equilibrium point during the pickling process. The pickling efficiency of bamboo shoots under PVPP technology increased by 34.1% compared to the traditional control groups. Meanwhile, the uniform salt distribution under PVPP technology also obtained better performance in comparison with the traditional groups. The pH value declined slowly from 5.96 to 3.70 with the extension of pickling time and sour flavor accumulated progressively. No significant differences were found in the color values (L*, a*, and b*) and the crunchiness of the bamboo shoot under different salt solution concentrations, vacuum pressure, and pulsation frequency ratio conditions. Colony-forming unit of lactic acid bacteria (CFU of LAB) decreased, to begin with, and then increased until the 6th day, followed by a declining trend in volatility. The nitrate content of bamboo shoots samples under PVPP treatments did not exceed the safety standard (<20 mg/kg) during the whole fermentation process, which proves the safety of PVPP technology. In conclusion, PVPP technology can safely replace the traditional method with better quality performance. The optimal PVPP processing conditions (vacuum pressure 60 kPa, 10 min vacuum pressure time vs. 4 min atmospheric pressure time, salt solution concentration 6%) have been recommended for pickling bamboo shoots with high product quality.